Influence Of Nitrogen Sources On Growth Profile And Their Kinetic Studies In Newly Isolated Acidophilic Microalgae, Coccomyxa Dispar And Scenedesmus Parvus - Lee, Zi Xin (Universiti Sains Malaysia, 2020)
Microalgae are potential candidates to be sustainably developed in the future as a new energy resource. However, low biomass production remains a big challenge to be tackled. Several factors had been tested to increase biomass production including abiotic and biotic factors. Nitrogen is the macronutrient in which uptake is of particular importance. This is because by supplying suitable nitrogen sources, metabolic pathways can be manipulated thus expand the production capabilities of microalgae. Despite many studies conducted on effect of nitrogen sources in different microalgae species, there is still limited information on Coccomyxa dispar and Scenedesmus parvus. Thus, this research is conducted to determine the influence of nitrogen sources on two acidophilic microalgae strains, Coccomyxa dispar and Scenedesmus parvus through cultivating them in nitrogen-deficient Bold Basal Medium (BBM) supplemented with 0.1% w/v ammonium sulphate, sodium nitrate and urea.